Energy transition in the European Union – institutional and legal factors - Rosicki, Remigiusz (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2023)
The subject of the research problem addressed in the article concerns the importance of institutional and legal (or, more broadly, political) factors of energy transition in the European Union. Following Aleh Cherp and his team, political factors are understood as state objectives, political interests and institutional capabilities and factors of other types. All of them, as a whole, enter into a relationship with other factors, such as socio-technical and techno-economic ones. Referring to F. W. Geels, the European Union can be defined as a kind of socio-technical regime (energy regime), responsive to internal or external threats or adverse events. The main purpose of the analysis is to present the relationship between the institutional and legal, socio-technical, and techno-economic factors. In order to specify the research problem, the research question has been posed of the extent to which institutional and legal factors affect energy transition in the European Union. To answer this question, the analysis relies on the theoretical aspects of energy transition studies, the institutional and legal approach and secondary statistical data. Zakres przedmiotowy problemu badawczego tekstu dotyczy znaczenia czynników instytucjonalno-prawnych, szerzej ujmowanych jako polityczne, transformacji energetycznej w Unii Europejskiej. Przez „czynniki polityczne” rozumie się – za A. Cherpem i zespołem – cele państwowe, interesy polityczne oraz możliwości instytucjonalne i czynniki innego typu. Wszystkie one, jako całość, pozostają w relacji z innymi, do których należy zaliczyć: społeczno-techniczne i techniczno-ekonomiczne. Z kolei za F. W. Geelsem Unię Europejską można określić mianem swoistego reżimu społeczno-technologicznego (reżimu energetycznego), responsywnego wobec wewnętrznych lub zewnętrznych zagrożeń albo zdarzeń niepożądanych. Głównym celem analizy jest prezentacja relacji, jaka występuje między czynnikami: instytucjonalno-prawnym i społeczno-technologicznym oraz techniczno-ekonomicznym. W celu uszczegółowienia zakresu przedmiotowego problemu badawczego w tekście wskazano następujące pytanie badawcze: „W jakim stopniu czynniki instytucjonalno-prawne wpływają na transformację energetyczną w Unii Europejskiej?”. Aby odpowiedzieć na to pytanie, analizę w tekście oparto na teoretycznych aspektach studiów nad transformacją energetyczną, ujęciu instytucjonalno-prawnym oraz wtórnych danych statystycznych.
Czynniki instytucjonalno-prawne transformacji energetycznej w Unii Europejskiej
Keywords: energy policy; institutionalization of energy policy; energy transition; energy transformation; European Union; polityka energetyczna; instytucjonalizacja polityki energetycznej; tranzycja energetyczna; transformacja energetyczna; Unia Europejska